2016
DOI: 10.3390/ijms17091533
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Porcine Pluripotent Cells: From ICM to iPSCs

Abstract: Abstract:Pigs have great potential to provide preclinical models for human disease in translational research because of their similarities with humans. In this regard, porcine pluripotent cells, which are able to differentiate into cells of all three primary germ layers, might be a suitable animal model for further development of regenerative medicine. Here, we describe the current state of knowledge on apoptosis in pluripotent cells including inner cell mass (ICM), epiblast, embryonic stem cells (ESCs), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…A key mediator acting in the apoptosis pathway is the tumour suppressor protein, p53. It has been found that p53‐induced intrinsic pathway occurs during the iPSCs generation and p53‐mediated regulation of the ratio of Bax versus Bcl‐2 protein level can influence the fate of a cell in response to stress (Kim & Hyun, ). Administration of Valproic acid, a HDACi, protected the cells from reprogramming‐induced senescent stress by inhibiting apoptosis through the suppression of the p16/p21 pathway (Zhai et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key mediator acting in the apoptosis pathway is the tumour suppressor protein, p53. It has been found that p53‐induced intrinsic pathway occurs during the iPSCs generation and p53‐mediated regulation of the ratio of Bax versus Bcl‐2 protein level can influence the fate of a cell in response to stress (Kim & Hyun, ). Administration of Valproic acid, a HDACi, protected the cells from reprogramming‐induced senescent stress by inhibiting apoptosis through the suppression of the p16/p21 pathway (Zhai et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A key mediator acting in the apoptosis pathway is the F I G U R E 2 Determination of apoptotic and total nuclei in cloned and IVF blastocysts by TUNEL assay tumour suppressor protein, p53. It has been found that p53-induced intrinsic pathway occurs during the iPSCs generation and p53-mediated regulation of the ratio of Bax versus Bcl-2 protein level can influence the fate of a cell in response to stress (Kim & Hyun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis plays important roles in mammalian oocyte maturation and preimplantation embryonic development [68]. In the latter context, apoptosis may contribute to embryonic loss [69] and affect some cellular responses [70] in embryos produced both in vitro and in vivo. ER stress-induced apoptosis has been reported in mammalian oocytes and IVM-derived embryos.…”
Section: Endoplasmic Reticulum Stress Induces Apoptosismentioning
confidence: 99%